PENGARUH MOTIVASI DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKUNTANSI FEB UNISMA ANGKATAN 2014/2015 - Devit Pranoto; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACT The purpose of this study is to know : 1) the influence of motivation and entrepreneurship education on entrepreneurship interests,2) the influence of motivation on entrepreneurship interests,3) the influence of entrepreneurship education on entrepreneurship interests. This research includes casual associative type using purposive sampling method. The population in this study is all students of Accounting Study Program Faculty of Economics and Business of University of Islam Malang force 2014/2015 by taking sample amounted to 130 respondents. Data were obtained by distributing questionnaires. The results of this study indicate: 1) motivation and entrepreneurship education have a positive and significant impact on the entrepreneurship interest in accounting students faculty of economics and business UNISMA force 2014/2015,2) Motivation has a positive influence on entrepreneurship interest in accounting students faculty of economics and business UNISMA force 2014/2015,3) Entrepreneurship education has a positive influence on entrepreneurship interest in accounting students faculty of economics and business UNISMA force 2014/2015. Keywords : motivation, entrepreneurship education, entrepreneurship interest